PENINGKATAN HASIL BELAJAR IPA TENTANG GAYA MAGNET MELALUI MODEL PEMBELAJARAN KOMPERATIF TIPE STAD PADA SISWA KELAS VA SDN 010 BAYUR SAMARINDA UTARA. - Afdal Afdal (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
This study aims to determine the increase of science learning outcomes about magnetic force through STAD Type Comparative learning model in the students of VA SDN 010 Bayur North Samarinda class. The number of students in this study was 32 people consisting of 17 men and 15 women.This classroom action research was conducted in three cycles following Arikunto flow which was implemented in SD Negeri 010 Bayur second semester of learning year 2016/2017 with total students 32 people. Research begins in January 2017 to February 2017. The research consists of: the ability to cooperate, communicate, student activeness and mastery of concepts. This study uses STAD method is considered the simplest and most direct of the cooperative learning approach by using small groups of 4-5 students in a heterogeneous way, thus creating an atmosphere that encourages students to need each other, dialogue between groups so it is easier to learn among students, Maintain true opinions and tolerance.In understanding the magnet by the students of VA class SD Negeri 010 Bayur Samarinda Utara with the criterion of learning mastery is 70. In cycle I with the average value obtained is 76.85 (percentage mastery 87.09%), to cycle II to become 87 , 28 (percentage of completeness 100%) with very good criteria. Similarly cycle II to cycle III has increased to 97.28 (percentage mastery 100%) very good criteria. Cycle I activity of student and researcher is enough, second cycle activity of student and researcher is good, cycle III student activity is good and research activity is very good. It can be concluded that this research is planning and evaluation of magnetic style learning model of STAD Co-operative Model where increasingly active teacher to increase student's learning interest increase student's learning outcomes.